Tuberous sclerosis associated lymphangioleiomyomatosis: a case report - Mushir, Aiman; Sohail Akhtar; Mujahid Hussain (Journal of the Pakistan Medical Association, 2023)
Lymphangioleiomyomatosis (LAM) is a multisystem disorder that primarily affects the lung. Tuberous sclerosis complex (TSC) is characterized by multiple benign tumours of the skin, brain, eyes, heart, lung, liver, and kidney. LAM can be either sporadic (sporadic-LAM) or in association with Tuberous Sclerosis (TSC-LAM). Many clinical, radiologic, and pathologic features are shared between TSC and sporadic variants. We present a case admitted at The Indus Hospital Karachi with pneumothorax and multiple manifestations of TSC-LAM. Keywords: Tuberous sclerosis, (Lymphangioleiomyomatosis), Cysticlungdisease, (Pneumothorax),Genetics.